2018
DOI: 10.1016/j.ifset.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HHP processing on volatile profile and sensory acceptance of Pêra-Rio orange juice

Abstract: The purpose of this study was to evaluate volatile compounds and sensory acceptance of HHP processed orange juice compared with non-processed and pasteurized orange juices. RSM and sniffing were successfully applied for optimization of HS-SPME conditions. The chosen HS-SPME conditions 37°C during 25 min of exposure properly characterized the volatile profile of HHP processed, pasteurized and non-processed orange juices. HHP processing conditions had an impact on the volatile profile of the juice. Sensory accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…The headspace solid‐phase microextraction (HS‐SPME) combined with GC‐MS was conducted to analyze the volatile compounds of sugarcane juice based on the procedure described in a previous study (Mastello, Janzantti, Bisconsin‐Júnior, & Monteiro, 2018). An SPME fiber (50/30 µm, DVB/CAR/PDMS, Supelco, Bellefonte, PA, USA) was chosen to extract the volatile compounds from the sugarcane juice.…”
Section: Methodsmentioning
confidence: 99%
“…The headspace solid‐phase microextraction (HS‐SPME) combined with GC‐MS was conducted to analyze the volatile compounds of sugarcane juice based on the procedure described in a previous study (Mastello, Janzantti, Bisconsin‐Júnior, & Monteiro, 2018). An SPME fiber (50/30 µm, DVB/CAR/PDMS, Supelco, Bellefonte, PA, USA) was chosen to extract the volatile compounds from the sugarcane juice.…”
Section: Methodsmentioning
confidence: 99%
“…[11] When the juice is heated during pasteurization, a complex series of chemical reactions occur, leading to losses of volatile compounds, which can affect the aroma of the product. [6,12] The HPP treatment could enhance or retard enzymatic and chemical reactions, which could lead to changes in the overall aroma profile. [7,12] In summary, the esters and alcohols were the main aroma compounds in the FPJ, while HPP treatments could better preserve the flavor quality of the FPJ than the TP treatment.…”
Section: Treatmentmentioning
confidence: 99%
“…This is due to its limited effect on the covalent bonds of low molecular-mass compounds, ensuring the safety of food products, as well as the retention of maximum freshness. [10,11] Previous studies have reported on the application of HPP in various fruit and vegetable products such as orange juice, [12] green asparagus juice, [6] mulberry juice, [13] pomegranate juice, [5,11] , and blueberry juice. [14] Researchers focused on the effects of HPP on the anthocyanins, color, antioxidant capacity, and total phenols, as well as the inactivation of microorganisms or enzymes in those juices.…”
Section: Introductionmentioning
confidence: 99%
“…The terms used were: watery, orange color, fruit, overripe, acid, natural, cloudy, transparent, cooked flavor (Lee et al, ), bitter, artificial, sweet smell, citric, sweet (Pineli, Aguiar, Fiusa, et al, ), for kids, cheap, expensive, breakfast (Cardinal, Zamora, Chambers, Carbonell Barrachina, & Hough, ). In addition, we used scientific criteria attributed to orange juice, such as nutritive, healthy, vitamin C (O'Neil, Nicklas, Rampersaud, & Fulgoni, ), durability (Mastello, Janzantti, Bisconsin‐Júnior, & Monteiro, ), tasty (Kim, Lee, Kwak, & Kang, ), sugar (MacGregor & Hashem, ; Shefferly, Scharf, & DeBoer, ), high calorie (Van Grieken, Renders, van de Gaar, Hirasing, & Raat, ), preservative (Zengin, Yüzbasıoglu, Ünal, Yilmaz, & Aksoy, ), unhealthy (DeChristopher, Uribarri, & Tucker, ; Shefferly et al, ), chemical (Linke, Casagrande, & Cardoso, ; Zhang & Ma, ), sustainable (Aschemann‐Witzel, ).…”
Section: Methodsmentioning
confidence: 99%